1996
DOI: 10.1002/hep.510230541
|View full text |Cite
|
Sign up to set email alerts
|

Long-term octreotide treatment prevents vascular hyporeactivity in portal-hypertensive rats

Abstract: Chronically portal-hypertensive rats show in vitroNatural somatostatin and its long-acting analogue vascular hyporeactivity in large part mediated by the octreotide 8 are increasingly used as vasoconstrictive endothelium-derived vasodilator nitric oxide. We tested agents in the treatment of variceal hemorrhages. 9-11 whether long-term octreotide treatment (15 mg/kg sub-Additionally, long-term octreotide treatment has recutaneously in 5% D/W, 8-hourly) corrects the in vitro cently been shown to prevent the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
1
35
2
Order By: Relevance
“…22,35,36 The mechanism is not well defined, but a direct action of octreotide on vascular smooth muscle tone in splanchnic resistance vessels of portal hypertensive rats seems unlikely. 37,38 Also, a direct inhibitory effect of octrotide on nitric oxide secretion in the splanchnic vascular epithelium has been ruled out. 37 However, the experimental studies on the effects of octreotide on vascular reactivity have all been performed on splanchnic vessels, and a direct effect of octreotide in other areas of the vasculature has indeed been suggested by a recent study in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,35,36 The mechanism is not well defined, but a direct action of octreotide on vascular smooth muscle tone in splanchnic resistance vessels of portal hypertensive rats seems unlikely. 37,38 Also, a direct inhibitory effect of octrotide on nitric oxide secretion in the splanchnic vascular epithelium has been ruled out. 37 However, the experimental studies on the effects of octreotide on vascular reactivity have all been performed on splanchnic vessels, and a direct effect of octreotide in other areas of the vasculature has indeed been suggested by a recent study in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Also, a direct inhibitory effect of octrotide on nitric oxide secretion in the splanchnic vascular epithelium has been ruled out. 37 However, the experimental studies on the effects of octreotide on vascular reactivity have all been performed on splanchnic vessels, and a direct effect of octreotide in other areas of the vasculature has indeed been suggested by a recent study in cirrhotic patients. 10 In addition, the experimental studies indicate that an inhibitory effect of octreotide on renin-aldosterone secretion as well as normalization of arginin-vasopressin may be responsible for the beneficial effects on sodium excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a different and more complex therapeutic strategy has recently been proposed in these patients to potentiate the effects of vasoconstrictors on the splanchnic vascular bed, such as a long-term administration of the drug (i.e., terlipressin) 30 and its combined use with albumin solution 31 or with an inhibitor of endogenous vasodilators. As far as the potential effectiveness of inhibitors of endogenous vasodilators is concerned, it should be underscored that experimental data showed that octreotide, 32 an inhibitor of glucagon release, as well as nitric oxide inhibition may reverse the arterial hyporeactivity in portal hypertensive rats. 33,34 In particular, nitric oxide inhibition was shown to reverse both the in vitro hyporeactivity to ␣-adrenergic agents in portal hypertensive rats 33 and the hyperdynamic circulation and renal sodium and water retention in vivo in rats with cirrhosis and ascites.…”
Section: Discussionmentioning
confidence: 99%
“…This has been well demonstrated with glucagon, 4 and also with NO. 40 Moreover, it has been demonstrated that octreotide may inhibit the release of tumor necrosis factor ␣, 20 another NO synthase inductor.…”
Section: Discussionmentioning
confidence: 99%